Molecular Detection of Tick-Borne Pathogen Diversities in Ticks from Livestock and Reptiles along the Shores and Adjacent Islands of Lake Victoria and Lake Baringo, Kenya - Omondi, David; Masiga, Daniel K.; Fielding, Burtram C.; Kariuki, Edward; Ajamma, Yvonne Ukamaka; Mwamuye, Micky M.; Ouso, Daniel O.; Villinger, Jandouwe (Frontiers in Veterinary Science, 2017)
Although diverse tick-borne pathogens (TBPs) are endemic to East Africa, with recognized impact on human and livestock health, their diversity and specific interactions with tick and vertebrate host species remain poorly understood in the region. In particular, the role of reptiles in TBP epidemiology remains unknown, despite having been implicated with TBPs of livestock among exported tortoises and lizards. Understanding TBP ecologies, and the potential role of common reptiles, is critical for the development of targeted transmission control strategies for these neglected tropical disease agents. During the wet months (April-May; October-December) of 2012-2013, we surveyed TBP diversity among 4,126 ticks parasitizing livestock and reptiles at homesteads along the shores and islands of Lake Baringo and Lake Victoria in Kenya, regions endemic to diverse neglected tick-borne diseases. After morphological identification of 13 distinct Rhipicephalus, Amblyomma and Hyalomma tick species, ticks were pooled (≤8 individuals) by species, host, sampling site and collection date into 585 tick pools. By supplementing previously established molecular assays for TBP detection with high-resolution melting analysis of PCR products before sequencing, we identified high frequencies of potential disease agents of ehrlichiosis (12.48% Ehrlichia ruminantium, 9.06% Ehrlichia canis), anaplasmosis (6.32% Anaplasma ovis, 14.36% Anaplasma platys, 3.08% Anaplasma bovis,) and rickettsiosis (6.15% Rickettsia africae, 2.22% Rickettsia aeschlimannii, 4.27% Rickettsia rhipicephali, 4.95% Rickettsia spp.), as well as Paracoccus sp. and apicomplexan hemoparasites (0.51% Theileria sp., 2.56% Hepatozoon fitzsimonsi, 1.37% Babesia caballi) among tick pools. Notably, we identified E. ruminantium in both Amblyomma and Rhipicephalus pools of ticks sampled from livestock in both study areas as well as in Amblyomma falsomarmoreum (66.7%) and Amblyomma nuttalli (100%) sampled from tortoises and Amblyomma sparsum (63.6%) sampled in both cattle and tortoises at Lake Baringo. Similarly, we identified E. canis in rhipicephaline ticks sampled from livestock and dogs in both regions and Amblyomma latum (75%) sampled from monitor lizards at Lake Victoria. These novel tick-host-pathogen interactions have implications on the risk of disease transmission to humans and domestic animals and highlight the complexity of tick-borne pathogen ecologies, which may include reptiles as reservoir species, in sub-Saharan Africa.